Red and Blue Liquid-Crystalline Borondipyrromethene Dendrimers - Mula, Soumyaditya; Frein, Stéphane; Russo, Virginie; Ulrich, Gilles; Ziessel, Raymond; Barberá, Joaquín; Deschenaux, Robert (My University, 2015)
We have designed a series of modular and fluorescent poly(arylester) dendrimers functionalized with cyanobiphenyl subunits and fluorescent borondipyrromethene (Bodipy) dyes. The green emitter is a Bodipy with four methyl groups, and the Bodipy dye possessing extended conjugation with two methyl and two vinyl groups acts as a red emitter. The design element of these architectures relates to a secondary amide linkers interposed between the conventional Bodipy and the dendrons. The second- and third-generation dendrimers give rise to nematic and/or smectic A phases, whereas the first-generation dendrimers show smectic A and C phases or an unidentified mesophase. The novel materials are highly fluorescent in solution and in the as-obtained powders but not in the mesophase. Dilution of the dendritic dyes with the nonfluorescent acid dendron in the solid phase shifted the fluorescence to higher energy, and demonstrated the presence of aggregates in the solid state. Mixing the red and blue materials in a solid phase led to the observation of effective electronic energy transfer from the red dye to the blue one. Increasing the proportion of the red dye (energy donor) from 1 to 250 molar with respect to the blue dye (energy acceptor) resulted in the observation of residual emission of the red dye in the solid state mixture. Increasing the proportion from 1 to 1000 resulted in equal emission in the 540 to 760 nm range.